Mediatizing Security: Examining the efficacy of WhatsApp-Based Communication on the Crime Response Efficiency of the Àmọ̀tẹ́kùn Corps in Ondo and Ekiti States, Nigeria - Ajayi Taiwo Peter (Universitas Negeri Yogyakarta, 2026)
The heightened insecurity in Nigeria necessitated the establishment of the Àmọ̀tẹ́kùn Corps in the southwestern region. Within this context, it becomes important to examine the role of WhatsApp, a widely adopted communication platform, in supporting the Corps’ efforts to address security challenges. Despite its growing relevance, there remains a notable gap in research providing a comprehensive assessment of how the Àmọ̀tẹ́kùn Corps’ use of WhatsApp has contributed to reducing insecurity in the region. Anchored on the Ritual View of Communication theory, this study focused on two southwestern states: Ondo and Ekiti. A case study design was adopted, with interviews serving as the primary data collection instrument. Eleven Àmọ̀tẹ́kùn officers across different ranks and units participated in the study. Findings indicate that the Corps in both states prefers WhatsApp for internal communication, information dissemination, and grassroots sensitization. The platform also facilitates interaction with local government authorities and landlord associations, enabling prompt feedback and intelligence gathering. Additionally, WhatsApp has been instrumental in disseminating safety and security information to the public. The study concludes that WhatsApp is an effective communication tool for the Àmọ̀tẹ́kùn Corps at the grassroots level and recommends its continued use as an auxiliary technology to mitigate insecurity.